2015
DOI: 10.1177/0956797615578476
|View full text |Cite
|
Sign up to set email alerts
|

Roots and Benefits of Costly Giving

Abstract: Altruism, although costly, may promote well-being for those who give. Costly giving by adults has received considerable attention, but less is known about the possible benefits, as well as biological and environmental correlates, of altruism in early childhood. In the current study, we present evidence that children who forgo self-gain to help others show greater vagal flexibility and higher subsequent vagal tone than those who do not, and children from less wealthy families behave more altruistically than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 38 publications
7
60
2
2
Order By: Relevance
“…Self-Reports of socio-emotional dispositions were also uncorrelated to vuLP R and only weakly related to Altruistically Motivated Behavior (also see Böckler et al, 2016). Our findings are in line with previous studies that have demonstrated associations between incidental HF-HRV upregulation and altruistically motivated behavior (Miller et al, 2015;Barrazza et al, 2015), whereas no such association has been reported for trait measures of socio-emotional dispositions based on self-report. Taken together, our data indicate that the propensity to upregulate HF-HRV is primarily related to social behaviors which are oriented towards the well-being of others (i.e., altruistic acts, cf., Batson, 2014), not other types of prosocial behavior which are not based in altruistic motivation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Self-Reports of socio-emotional dispositions were also uncorrelated to vuLP R and only weakly related to Altruistically Motivated Behavior (also see Böckler et al, 2016). Our findings are in line with previous studies that have demonstrated associations between incidental HF-HRV upregulation and altruistically motivated behavior (Miller et al, 2015;Barrazza et al, 2015), whereas no such association has been reported for trait measures of socio-emotional dispositions based on self-report. Taken together, our data indicate that the propensity to upregulate HF-HRV is primarily related to social behaviors which are oriented towards the well-being of others (i.e., altruistic acts, cf., Batson, 2014), not other types of prosocial behavior which are not based in altruistic motivation.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, we corroborate earlier findings on a relationship between increases in HF-HRV and altruistic behavior (Barraza et al, 2015;Miller et al, 2015). Unlike earlier studies which employed a single task to index altruism, our measure relies on a validated multimethod factor score of altruistic behavior across a variety of tasks (Böckler et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations